Piezoelectric Transducers Materials, Devices and Applications - Sanchez-Rojas, Jose Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Advances in miniaturization of sensors, actuators, and smart systems are receiving substantial industrial attention, and a wide variety of transducers are commercially available or with high potential to impact emerging markets. Substituting existing products based on bulk materials, in fields such as automotive, environment, food, robotics, medicine, biotechnology, communications, and other technologies, with reduced size, lower cost, and higher performance, is now possible, with potential for manufacturing using advanced silicon integrated circuits technology or alternative additive techniques from the mili- to the nano-scale. In this Special Issue, which is focused on piezoelectric transducers, a wide range of topics are covered, including the design, fabrication, characterization, packaging, and system integration or final applications of mili/micro/nano-electro-mechanical systems based transducers.